2021
DOI: 10.3390/pr9112049
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Microbial Flora in Dry Aged Beef to Evaluate the Rancidity during Dry Aging

Abstract: Dry aging creates a unique taste and flavor in beef; however, the process also causes rancidity, which is harmful to humans. During dry aging, the microbial flora in beef changes continuously; thus, this change can be used as an indicator of rancidity. The objective of this study was to analyze the correlation between microbial flora in beef and rancidity during dry aging. The round of beef (2.5–3 kg) was dry aged under 1.5 ± 1 °C and 82 ± 5% moisture for 17 weeks. The microflora in the dry aged beef was analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
0
14
1
Order By: Relevance
“…Lactobacilli dominate under anaerobic conditions and Pseudomonas species dominate under aerobic conditions (Kim et al, 2021). In the present study, LAB counts showed no differences regardless of aging method or aging time except for wet aging.…”
Section: Microbial Analysiscontrasting
confidence: 46%
See 3 more Smart Citations
“…Lactobacilli dominate under anaerobic conditions and Pseudomonas species dominate under aerobic conditions (Kim et al, 2021). In the present study, LAB counts showed no differences regardless of aging method or aging time except for wet aging.…”
Section: Microbial Analysiscontrasting
confidence: 46%
“…Microorganisms such as bacteria, yeasts, and molds can grow both on surface and inside of beef during long-term aging. They can metabolize ingredients of beef and produce various metabolites, resulting in unique flavors of beef ( Kim et al, 2021 ). On the other hand, they can also cause lipid peroxidation and off-flavor ( Kim et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The safety and quality characteristics of food can also be predicted by evaluating bacterial composition and growth during processing or storage. An example of this is the study by Kim et al [7], in which metagenomic tools were used to correlate rancidity and microflora in dry-aged beef. Using analysis and quantification of microflora by qRT-PCR, the authors demonstrated that increases in the number of Pantoea spp.…”
mentioning
confidence: 99%